Influence on the structural optical and electrical properties of cuprous iodide complexes with tetramethylethylenediamine - Zulkifly, Mohammad @ Ab Aziz (2019)
This study will attempt to overcome the strong tendency of cuprous iodide (CuI) to coalesce, rapidly deteriorates, and detaches from interfacial contacts by chelating the CuI with an aliphatic organic ligand known as N,N,N’,N’-tetramethylethylenediamine (TMEDA). Crystalline solids of CuI complexes with TMEDA is successfully synthesized from the saturated and homogenous solution of CuI in acetonitrile. The brown solids quickly turned to dark-blue once exposed to air indicating the air-sensitive nature of the compound. The FTIR confirms the presence of CH2, and CH3 functional group, while EDX analysis confirms the Cu2I2Tmeda2 stoichiometry of the complex compound. X-ray diffractogram peaks confirm the multi-crystalline nature of the solid which improved after 15 minutes of moderate heating at 80°C. Sample loses its crystallinity at 150 °Csuggesting a phase transition due to oxidation of CuI to CuO. The sharp peaks at (111) and (200) orientations remained after the complexation demonstrating that some of the CuI structure is retained. The FESEM observation shows the presence of monoclinic shaped grains as reported in the literatures, with an average agglomerated grain size of 3.03 μm as well as more uniform FTO coverage than the bare CuI sample. TEMs observation reveals the spherically shaped and agglomerated TMEDA nanoparticles shielding the much smaller CuI nanoparticles. Optical spectroscopy indicates good UV absorbance, high transparency over the visible range, and direct band gap energy of ~2.4eV at an annealing temperature of 90 °C. Doubling the solution concentration lowers theband gap energy by ~ 0.24 eV. Impedance spectroscopy suggest a diffusion-recombination model with low frequency Warburg feature, hole transport resistance of 190 Ω, recombination resistance of 5.73 kΩ, and electron lifetime of 3.16 μs which improves by two orders of magnitude when the concentration doubles at 0.5 V forward bias. The findings suggest this material is potentially useful as hole transport medium.